MODELING A NEGOTIATION PROCESS BETWEEN AIRCRAFT USING PETRI NETS - Daria ŻUCHOWSKA; Anna STELMACH (Scientific Journal of Silesian University of Technology. Series Transport)
New air traffic control ideas are sought. Many studies point out the delegation of the responsibility for ensuring separation from air traffic controllers to the aircraft crews, but it should be assumed that the transition from centralized to decentralized air traffic control will occur in stages. It is, therefore, necessary to ensure effective communication between conflicting aircraft and to define the negotiation process between aircraft. The concept of the process of negotiation and communication between aircraft in conflict using a monotonic concession protocol is presented. The proposed solution was modeled using a Petri Net, which allowed us to analyze all the dependencies present in the system. The analysis allowed us to evaluate the method in the context of safety. The conducted research showed that, under the assumed conditions, the negotiation method allows obtaining the desired effect of negotiations while maintaining an adequate level of safety.